Hydrolysed insect proteins as fish meal alternatives in the diets of South African abalone (Haliotis midae) - Van Schalkwyk, Mighael (Stellenbosch : Stellenbosch University, 2023)
Thesis (MScAgric)--Stellenbosch University, 2023.